Mathematical Model for Transmission and Control of Covid-19 in Human Population of Kigezi Sub-region. - Mukamatayebwa, Keneth (Kabale University, 2025)
In this research, an SEIR model is based on the fact that it describes the transmission dynamics of COVID-19 virus disease in humans, mainly from the Kigezi subregion. The model suggests that S stands for susceptible, E stands for exposed, I stands for infected, and finally, R stands for removed or recovered from the system. The parameters such as B indicates the entry of a new population into the system of the model, β indicates the rate at which the susceptible individuals are exposed to the disease, n shows the infection rate, μ natural death rate, t recovery rate, and α shows the death resulting from the disease. When analyzing the disease-free equilibrium, we equate the susceptible to zero such that, for the rest, we set them to be zero ie, E = 0, I = 0, and R = 0, and thereafter we obtain {So,Eo, Io,Ro} = { }. At disease equilibrium, and from there we analyze the equilibrium points of each stage. The basic reproductive number R0 is given by FV-1 where F and V are matrices obtained from fx and vx and where Fx is newly infected and Vx is the other term. The sensitivity index shows the effect of each parameter used in the equation and how it can affect the results of the model, therefore it's obtained from the given formula as R0 = where R0 is the basic reproductive number and P indicates any parameter used in the model formulation